Hubungan Antara Determinan Sosial Dan Pengetahuan Dengan Upaya Pencegahan Penularan Penyakit Tuberkulosis (Tbc) Di Puskesmas Panjang Kota Bandar Lampung - Jefri Irawan; Dyah Wulan Sumekar Rengganis Wardani; Betta Kurniawan (Medula, 2026)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The primary symptom of TB is a cough with phlegm that lasts for two weeks or more. The general objective of this study was to determine the relationship between social determinants and knowledge of TB transmission prevention efforts at Panjang Community Health Center, Bandar Lampung. This was an analytical cross-sectional study, with samples comprised of TB patients registered at Panjang Community Health Center between December and January 2022 and meeting the inclusion criteria. The sampling technique used total sampling. Data were obtained using a questionnaire. Data were analyzed using the Chi-square test. Low income, low education (elementary and junior high school), have a job, belong to the lower social class group, are male and have good knowledge. The results of statistical tests show a significant relationship between income and efforts to prevent TB transmission (p-value = 0.034), There is no significant relationship between education level (p-value = 0.076), employment (p-value = 0.079) and efforts to prevent TB transmission, and there is a significant relationship between class (p-value = 0.026), gender (p-value = 0.017), knowledge (p-value = 0.000) and efforts to prevent TB transmission. There is a relationship between social determinants and knowledge and efforts to prevent tuberculosis (TB) transmission at Panjang Community Health Center, Bandar Lampung City.